Rheological and Morphological Properties of Blood vs. Vibration Exercises (Smovey®)—A Preliminary Study on Elderly Women - Aleksandra Kiełtyka-Słowik; Aneta Teległów; Joanna Gradek (Applied Sciences)
Background: Physical activity in elderly adults reduces the risk of numerous diseases, enhances their quality of life, and improves their physical performance and overall strength. This study aimed to evaluate the effects of smovey® exercise on morphological and rheological blood parameters in a group of women over 60 years of age. Methods: The study included 30 women aged 71.08 ± 6.41 years, with a control group of 15 age-matched women. Participants in the experimental group underwent a three-month smovey® training program, consisting of two 45 min sessions per week. The control group did not engage in any regular physical activity. Blood samples were collected from the experimental group before and after the training period, while in the control group, blood was collected once. Results: After three months of smovey® training, a statistically significant increase in red blood cell, hemoglobin, and platelet counts was observed. Smovey® training also enhanced erythrocyte deformability at the lowest shear force. Conclusions: Smovey® training leads to changes in the morphological properties of blood in elderly women, leading to increases in RBC, HGB, PLT, and MCHC indices. Additionally, smovey® training improves erythrocyte deformability at a shear stress of 0.30 [Pa], reducing the half-time of complete aggregation.